A Research on Sexual Harassment among Schools Youngsters (Journal of Population and Development, 2023)
Sexual harassment exists throughout the world. According to various studies, approximately 15 million adolescent girls worldwide have experienced forced sexual intercourse or other sexual acts at some point in their life. Out of these, 9 million adolescent girls were victimized within the past year. Based on data from 30 countries, only one per cent ever sought professional help (UN Women, 2018). Despite of the severity of the problem, it has not yet received the attention it should. The lack of researches in these areas is also one of the major reasons for the failure of effective measures to tackle these problems. Sexual harassment is not well received as sexual abuse or rape or sexual violence because it doesn’t produce as severe consequence as the latter ones do. This article based on the research on schools of Godawari Muncipality ward No.3 of Lalitpur district and followed by exploratory research design. For quantitative information, interview schedule was used. Only 50 adolescent students both boys and girls were selected for the respondents. The findings show that almost all the respondents have known the types and forms of sexual harassment. Almost all of the respondents have felt harassed once in their lifetime. Girls are the easiest target for harassment. Mostly, perpetrators are mainly stranger and held in public places but some respondent share being harassed by their own relatives and known person like school teachers, friends. Male victims were less like to report cases as they feel humiliation in this male-dominated society. Most of the females also find not reporting cases as they fear of questioned by society of their characters. It is very important to aware from sexual harassment from young age and strict laws should be implemented regarding the sexual harassment.